The Role of Mobile Technology in Enhancing Classroom Interaction for Accounting Instructors in Higher Vocational Education - Wang, Lipeng (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The rapid advancement of mobile technology has introduced new opportunities to enhance classroom interaction, particularly in higher vocational accounting education, where theory and practices are closely integrated. Traditional interaction modes often limit student engagement and participation due to constraints of time, space, and format. This study addresses the gap in research on the interactive behaviors of accounting instructors under mobile network environments, focusing on two key aspects: (1) analyzing the effectiveness and influencing factors of mobile technology in facilitating instructor-student interactions in various teaching contexts, and (2) developing a predictive model using data mining techniques to forecast instructor interaction behaviors. By providing data-driven insights and a theoretical foundation, this study aims to optimize classroom interaction, improve teaching quality, and contribute to educational reform in accounting education.